Epidemic Characteristics of COVID-19 in Africa - Wang, Lijun; Dong, Shengwen; Zhao, Ying; Gao, Yulei; Wang, Jian; Yu, Muming; Xu, Fei; Chai, Yanfen (Frontiers in Physics, 2020)
Objectives: To investigate COVID-19 epidemic characteristics in Africa and provide some references to prevent pandemic. Methods: We collect information of the laboratory-confirmed case of COVID-19 that has been reported since April 28, 2020, in Africa, describe the epidemic characteristics in different regions of Africa, and predict the spread trend. Results: (1) There are 35,309 COVID-19 cases and 1,522 deaths in 54 African countries. Both case amount and death toll in Northern Africa are higher than those in other African regions, while case fatality rate (CFR) in Africa is lower than that of the world. (2) Among the 54 countries in Africa, 39 of them (72.22%) report confirmed cases between 1-499. (3) 596,146 tests have been conducted in 35 countries and 28,271 patients confirmed, with a positive rate of 4,74%. However, there are only 335 tests (interquartile range: 145.5-874) for every one million people in Africa. (4) The number of infection cases will increase to around 150,000 at the end of May according to our model. Conclusion: In Africa, COVID-19 spread faster while with a relatively lower CFR, and it may be related to higher young people ratio. In addition, test intensity of COVID-19 is obviously insufficient in Africa.